Response to letter regarding article, "The effect of selective heart rate slowing in heart failure with preserved ejection fraction" - Pal, N; Sivaswamy, N; Mahmod, M; Yavari, A; Rudd, A; Singh, S; Dawson, D; Francis, J; Dwight, J; Watkins, H; Neubauer, S; Frenneaux, M; et al. (American Heart Association, 2016)
We thank de Dios for their comments related to the differences in outcomes noted between our observations and previously published work.